Characterization and evaluation of sudanese fly ash as partial replacement for cement in concrete mixes (Journal of Building and Road Research, 2021)
The main objectives of this paperare to characterize the physical and chemical properties of the locally produced fly ash,to study its suitability to be utilized in concretemixes and to determine the degree of its pozzolanicity .Physical and chemical properties of fly ash were tested according to the standards of the American Society of Testing and Materials (ASTMC311-02). Fly ash was tested for density, fineness, moisture, Loss on Ignition (LOI), chemical composition, X-ray Fluorescence test (XRF), X-ray Diffraction test (XRD) and strength test. The results were then compared with the ASTM C618-03.It was found that the locally produced fly ash contains high level of silica, hence it can be classified, based on its chemicalcomposition, as class F fly ash; this may be probably due to the addition of sand applied in the combustion chamber. TheXRD showed that it contained crystalline form of silica which is not good for the use in concrete. On the other hand, thestrength test proved that there was a degree of strength and pozzolanicity obtained. The strength activity index of 28-daywas found 70%.This may be due to presence of amorphous silica within the crystalline one.
Keywords: sudanese fly; concrete